Analyzing the impact of business preference components on achieving e-city - Saeed Mohammadlou; Mohammad Mahdi Mozaffari; Babak Haji Karimi; Kamyar kavosh (تحقیقات کاربردی علوم جغرافیایی)
One of the concepts that is widely considered in all societies today, especially in developed countries, is the electronic city. The e-city is not an invention or an innovative proposal, but a reality that has shown its place based on the needs of today's society. The aim of this study was to analyze the effect of components of business preferences in achieving e-city. This research is applied in terms of purpose and descriptive-analytical method. Data collection tool was a researcher-made questionnaire whose validity was confirmed as qualitative and quantitative validity and its reliability was confirmed using Cronbach's alpha method and combined reliability. In this study, in order to analyze the research data from the software SPSS and Amose were used. Findings of this study showed that the variables of customer knowledge, customer focus, customer lifetime value, value creation, technology, useful interaction and communication quality have a positive and significant effect on the realization of e-city. Among the research variables, the customer-centric variable with a path coefficient of 0.38 had the most impact and the customer knowledge variable with a path coefficient of 0.19 had the least impact.